Comparison of sexual function scale scores in women according to the contraception method used as part of family planning strategy in Turkey - Banuhan Şahin; Görker Sel; Buğra Şahin; Şafak Hatırnaz (Clinical and Experimental Obstetrics & Gynecology, 2021)
Background: Continuation of sexuality is essential for a healthy partnership. However, the contraceptive method used by women of reproductive age may affect their sexual function. Aim: This study was aimed to compare sexual function scale scores in women according to the contraception method used as part of family planning strategy in Turkey. Methods: We surveyed sexually active women who used any contraceptive method served as family planning services in Turkey (ethinylestradiol/levonorgestrel pills, copper intrauterine device, condoms) and also tubal sterilisation, or coitus interruptus. Women completed an online questionnaire which asked for information on sociodemographic factors and sexual intercourse characteristics, including items from the Female Sexual Function Index (FSFI). A total FSFI score less than 26.55 was considered to indicate sexual dysfunction. Results: The questionnaire was completed by 242 women between the ages of 18 and 40 years. Condoms (34.7%) were the most frequent and tubal sterilisation (8.3%) was the least frequent contraception method among the women. The lowest total FSFI domain score was observed in the coitus interruptus group (24.31 ± 6.92), and scores for arousal, lubrication, orgasm, and pain subgroups were at the lowest levels in this group. Female sexual dysfunction (FSD) was mostly seen in women whose partner used the coitus interruptus method (P = 0.038). Conclusion: Women who used coitus interruptus had the highest rates of sexual dysfunction compared to all other women. The prevalence of FSD was very high in this traditional contraception method group, which may be attributed to the fear of getting pregnant. We conclude that counselling on modern contraception methods as part of family planning strategy in Turkey is an excellent way to enhance female sexuality.